The Utility and Acceptability of a Self-Help Smartphone Application for Eating Disorder Behaviors - Kim, Jane Paik (J Technol Behav Sci, 2018)
OBJECTIVE: Smartphone applications (apps) for eating disorders are a promising approach to assist individuals who do not receive traditional treatment. This study examines usage characteristics, perceptions regarding the acceptability of a new self-help intervention developed for users with eating disorders, and associations between attitudes and use patterns. METHODS: 189 individuals pilot-tested a personalized app-based program, and 133 completed the required components of the pilot-test over an 8-day period. Of these, 64 individuals (49%) completed an exit survey pertaining to acceptability. RESULTS: Seventy percent of those who pilot-tested the app-based program completed the required components, i.e. a baseline review and then a 1-week assessment. Body mass index was associated with the total number of recorded meal logs. Study participants rated the app as highly suitable and acceptable, providing evidence of the feasibility and appropriateness of the program. CONCLUSION: The app-based program demonstrated feasibility of deploying the app across user groups and high acceptability.